In this economy?: how money and markets really work - Scanlon, Kyla. (New York Crown Currency, 2024)
An illustrated guide to the mad math and terrible terminology of economics, from one of the internet's favorite financial educators. The stuff you really need to know about how the economy works? It's pretty simple. Yes, even if you were bored to tears in economics class, or if you're cross-eyed from reading painfully convoluted-or straight-up misguided-financial commentary. In this particularly disorienting era, many have turned to a young economic analyst named Kyla Scanlon for answers. Now, Scanlon is writing a definitive, approachable guide to the key concepts and mechanics of economics and the most common myths and fallacies to steer clear of. Through her trademark blend of creative analogies, clever illustrations, refreshingly lucid language-and even quotes from poetry, literature, and philosophy-she answers questions such as: What is Fed cred, Fed flexing, and Fedspeak? Is our national debt really a threat? What is a "mild" recession, exactly? What's really happening in the labor market, and how do we improve it for workers? At a time when experts overcomplicate simple things loudly, choosing to generate smoke rather than clearing the air, In This Economy? shows that understanding the markets-and the systems they operate in-is easier than you think. Whether you're worried about your mortgage rate, job security, bank account balance, or the health of the broader economy, this concise and witty guide will give you the confidence to make smarter financial decisions-no matter what the headlines say
Includes bibliographical references and index
Keywords: Economics